Penerapan Analisis SWOT dalam Meningkatkan Penjualan pada Restoran “Ayam Goreng Ananda” Jember - Sirmadani, Trisna Bela; Nurhasanah, Elsa Weres; Arifah, Naili Nur; Fuadah, Lina; Qomariah, Nurul (BUDGETING : Journal of Business, Management and Accounting, 2024)
The increasingly fierce level of business competition currently means that business actors need to have a strategy in order to survive and develop. Companies and MSMEs need to implement effective marketing strategies to increase sales to prepare themselves to face increasingly fierce competition from other competing businesses. By using a SWOT analysis, a business can determine what needs to be improved both internally and externally to ensure work operations run smoothly. This research aims to see the application of SWOT analysis to the factors that influence sales and to analyze the application of SWOT analysis in increasing sales volume at the "Ayam Goreng Ananda" restaurant. The method used in this research is a literature review method through a qualitative descriptive writing system and an interview method by interviewing the restaurant owner directly. The research results show that with this SWOT analysis, the strengths, weaknesses, opportunities and threats of Ananda Jember Fried Chicken MSMEs can be described. Keywords: Marketing Strategy, MSME, SWOT Analysis, Sale.